2020
DOI: 10.1108/tlo-12-2018-0205
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing innovation performance in higher education institutions

Abstract: Purpose The purpose of this paper is to explore the relationship between transformational leadership, knowledge management capabilities, organizational learning and innovation performance in the context of higher education institutions. Design/methodology/approach Using a survey research design, data was collected from 219 respondents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 59 publications
0
57
0
13
Order By: Relevance
“…Third, this study focused on the moderating role of transformational leadership, based on its characteristics such as leader's skills to design appealing visions, focus on goal setting and achievement, indulgence in coaching, training and development, creative problem-solving skills, and developing a complete sense of purpose [89], enhancing the link between entrepreneurial orientation and organizational commitment [7,9,52,60] and innovation performance [5,8,10,18,20,22,27,28,70,75]. Aimed at examining the direct effects of transformational leadership on innovation performance [82] and organizational commitment [83], past studies suggested the increase in performance [54,80,81]. The moderating role of transformational leadership on entrepreneurial orientation and innovation performance's relation was found to be positive [84]; therefore, this study examined the transformational leadership's moderation mechanism on the relationship between entrepreneurial orientation and organizational commitment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, this study focused on the moderating role of transformational leadership, based on its characteristics such as leader's skills to design appealing visions, focus on goal setting and achievement, indulgence in coaching, training and development, creative problem-solving skills, and developing a complete sense of purpose [89], enhancing the link between entrepreneurial orientation and organizational commitment [7,9,52,60] and innovation performance [5,8,10,18,20,22,27,28,70,75]. Aimed at examining the direct effects of transformational leadership on innovation performance [82] and organizational commitment [83], past studies suggested the increase in performance [54,80,81]. The moderating role of transformational leadership on entrepreneurial orientation and innovation performance's relation was found to be positive [84]; therefore, this study examined the transformational leadership's moderation mechanism on the relationship between entrepreneurial orientation and organizational commitment.…”
Section: Discussionmentioning
confidence: 99%
“…The four features of transformational leadership "idealized influence, inspirational motivation, intellectual stimulation and individualized consideration" significantly affect performance [54,80,81], innovation performance [82] and organizational commitment [83]. Engelen, Gupta [84] found that entrepreneurial orientation and innovation performance were moderated by transformational leadership using RBV, highlighting the importance of the transformational leadership's moderation mechanism on entrepreneurial orientation and organizational commitment.…”
Section: Moderating Role Of Transformational Leadershipmentioning
confidence: 99%
“…The Standardized Root Mean Square Residual (SRMR) is 0.077 (<0.08); it supports that the model in this study has an acceptable model fit. Hence, the SRMR result, R 2 values, reliability, and validity measures indicate that the study model is sufficient to assess the proposed hypothesized relationships as prior studies designate (Asiedu et al, 2020).…”
Section: Research Resultsmentioning
confidence: 88%
“…Above all, critical and periodic review of existing organizational boundaries and linkages is very crucial in promoting the process of innovation in an HEI. Asiedu et al (2020) emphasized knowledge management capabilities, organizational learning and innovation performance in the context of higher education institutions (HEIs).…”
Section: Innovations In Collaboration Processmentioning
confidence: 99%